Approach Higher Order Thinking-Problem Based Learning in Learning Mathematics Material Linear Equations Absolute Value One Variable - Anik Kirana; Siti Kholifah (INNOVATION RESEARCH JOURNAL, 2020)
In learning in schools there are still many teachers using a teacher-centered learning model orTeacher Center. In teacher-centered learning, the teacher can control or organize the material andtime completely, but communication only occurs in one direction so that learning runs passively.Teacher-centered learning conditions are not as expected in the 2006 Ministry of Education Regulation,which is expected to learn mathematics in students having the ability to think logically, analytically,systematically, critically, and creatively, and have the ability to work together. One learning modelthat can help students develop critical and logical thinking skills is Problem Based Learning (PBL). InPBL, the teacher's function is as a facilitator which means preparing all the facilities needed in learningactivities. PBL becomes better if it is associated with the approach Higher Order Thinking(HOT)because the estuary of higher-order thinking patterns is able to solve problems From theobservations of student learning activities the HOT-PBL approach includes activities namely: motoractivity, mental activity, and emotional activity students during learning take place in the classroomwith the HOT-PBL approach get a good category, which means students are classified as activestudents. While the results of the test which includes HOT-PBL questions obtained 85.7% masteryachievement which means that 85.7% of students achieved individual completeness.